Early inflorescence and floral development in Cocos nucifera L. (Arecaceae: Arecoideae) - Perera, Prasanthi I.P.; Hocher, V; Weerakoon, LK; Yakandawala, D.M.D.; Fernando, SC; Verdeil, JL (Elsevier, 2010)
Palms are generally characterized by a large structure with a massive crown that creates difficulties in anatomical studies. The flowering behaviour of palm species may be a useful indicator of phylogenetic relationships and therefore evolutionary events. This paper presents a detailed histological study of reproductive development in coconut (Cocos nucifera L.), from initiation up to maturation of staminate and pistillate flowers. Reproductive development in coconut consists of a sequence of individual events that span more than two years. Floral morphogenesis is the longest event, taking about one year, while sex determination is a rapid process that occurs within one month. The inflorescence consists of different ultimate floral structural components. Pistillate flowers are borne in floral triads that are flanked by two functional staminate flowers. The staminate flowers are born in floral diads towards the base of the rachilla followed by solitary flowers in the middle to top of the rachilla. Three primary phases were identified in reproductive development, namely, transition of axillary bud into inflorescence bud, formation of floral buds, and sexualisation of individual flower buds. All developmental events with respect to stage or time of occurrence were determined.